KASUS BUNUH DIRI PADA MASYARAKAT JEPANG (PENYEBAB DAN TREN DEWASA INI) - Sri Wahyu Istana Trahutami (KIRYOKU, 2017)
Japan holds the 3rd rank as the biggest suicide (jisatsu) nation in the world after Korea and Hungary with total 29.442 suicide cases based by the data released  by WHO in 2012. The biggest suicide cases occurred in 2008 with total casualties 34.000. The factor that trigger suicide are health issue, financial, and household problem.